FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN SEKTOR PROPERTIES & REAL ESTATE TAHUN 2019-2022 - Riki Yanto; Susanto Salim (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This research aims to examine the effect of profitability, leverage, liquidity, and firm size as independen variables on firm value as dependen variable in the properties & real estate sector listed on the Indonesia Stock Exchange (IDX) in 2019-2022. The research using purposive sampling method and collected 120 samples from 30 companies which meet the requirement. This research uses multiple regresion analysis with SPSS Program Version 21 and Microsoft Excel 2016 to find empirical evidence of influence simultaneously or partially. The result of simultaneous test shows that the variable profitability, leverage, liquidity, and firm size simultaneously have a significant effect on firm value. Based on the results of the partial test, it show that the profitability and leverage partially have a positive and significant effect on firm value. The result of partial test for the variable liquidity show that liquidity has a positive and insignificant effect on firm value. The result of the partial test for the variabel firm size show that firm size has a negative and insignificant effect on firm value.